Based on bioinformatics, SESN2 negatively regulates ferroptosis induced by ischemia reperfusion via the System Xc−/GPX4 pathway - Hu, Jiejie; Qin, Lijun; Zhu, Guoqiang; Ren, Jingjing; Wang, Hongxia; Jin, Jing; Zheng, Haixue; Li, Dan; Ge, Zhaoming (Frontiers in Genetics, 2025)
IntroductionCerebral ischemia–reperfusion (IR) causes severe secondary brain injury. Previous studies have demonstrated that ferroptosis is involved in IR-induced brain injury. However, whether IR induces ferroptosis in brain microvascular endothelial cells (BMVECs) is not fully understood.Materials and methodsOxygen–glucose deprivation/reoxygenation (OGDR) was performed in bEND.3 cells to mimic IR injury in vitro, and a focal cerebral IR model was created in C57BL/6 mice. Transcriptomic sequencing of the cells was performed first, followed by bioinformatics analysis. Differentially expressed gene (DEG) enrichment analysis highlighted ferroptosis-related pathways.ResultsUsing Venn analysis, nine ferroptosis-related DEGs were identified, namely, Slc3a2, Slc7a11, Ccn2, Tfrc, Atf3, Chac1, Gch1, Lcn2, and Sesn2. Protein–protein interaction (PPI) analysis combined with molecular complex detection (MCODE) identified six hub genes, namely, Ddit3, Atf3, Sesn2, Trib3, Ppp1r15a, and Gadd45a. Spearman’s correlation analysis revealed a significant correlation between the hub genes and ferroptosis-related DEGs. After reperfusion, the levels of ferroptosis indicators were elevated, and the expression of the ferroptosis-related proteins Xc− and GPX4 decreased. SESN2 is a hub gene and key antioxidant regulator. SESN2 silencing reduced the expression of System Xc− and GPX4, whereas overexpression of SESN2 promoted the expression of System Xc− and GPX4.DiscussionThese results suggest that SESN2 is a negative regulator of ferroptosis. Enhancing the expression of SESN2 can alleviate ferroptosis through the activation of the System Xc−/GPX4 pathway. By integrating bioinformatics analysis with mechanistic exploration, this study revealed that ferroptosis plays a crucial role in IR-induced BMVECs injury, with SESN2 acting as a negative regulator via the System Xc−/GPX4 pathway.